Experimental study on heat pipe thermoelectric generator for industrial high temperature waste heat recovery. (5th July 2020) - Wang, Chenglong; Tang, Simiao; Liu, Xiao; Su, G.H.; Tian, Wenxi; Qiu, Suizheng
Highlights: A novel Heat Pipe Thermoelectric Generator (HPTEG) for high temperature waste heat recovery is proposed. Laboratory scale HPTEG experiment setup is fabricated for passive heat transfer and static thermoelectric conversion. The isothermality of heat pipe in HPTEG is much better than that under directly cooling conditions. The effective thermal conductivity of heat pipe increases with the increasing of operation temperature. Effective Seebeck coefficient and thermal conductivity are employed to assess the TE performance of HPTEG. Abstract: The recovery of high-temperature waste heat is important for improving energy efficiency and environmental sustainability. In this paper, a novel high-temperature waste heat recovery system with heat pipe and thermoelectric generator (TEG) is proposed to resolve the mismatch between energy supply and demand. A Heat Pipe Thermoelectric Generator (HPTEG) experimental setup with potassium heat pipes and skutterudite TEGs is designed and fabricated to achieve passive thermal management and electricity generation. The passive heat transfer and thermoelectric performances are investigated. The effective thermal conductivity of the heat pipe is proposed to assess the heat pipe heat transfer performance. When the heat pipe temperature reaches 630 °C, the effective thermal conductivity reaches 35831 W/(mK), which is practically 100 times that of copper. An effective Seebeck coefficient and an effective thermal conductivity of the TEGs are proposed to evaluate the TEG system-level performances. The simulation accuracy of HPTEG system performances is significantly improved when the effective Seebeck coefficient and effective thermal conductivity are employed. Moreover, they can be utilized to accurately predict the HPTEG performance in actual engineering fields.